Overall cooling effectiveness of effusion cooled annular combustor liner at reacting flow conditions. (5th February 2018) - Ji, Yongbin; Ge, Bing; Chi, Zhongran; Zang, Shusheng
Highlights: Infrared thermography is used to measure temperature field on the combustor liner at reacting conditions. Flow rate ratio and equivalence ratio have a great effect on the overall effusion cooling effectiveness. Inclined effusion holes provide better cooling performance than normal holes. Abstract: A three-sector annular combustor test rig is built to carry out experimental investigation on the liner effusion cooling performance using steady state infrared radiation thermography method at reacting flow conditions. 7 rows of effusion holes in a staggered layout are distributed on both inner and outer liner bended testing plates, where the temperature field is captured and overall cooling effectiveness is analyzed. Coolant-to-main air flow rate ratio and equivalence ratio are varied to evaluate their effects on the cooling effectiveness. Three axial nozzles generating representative high swirling flows are fueled by methane-air mixture to perform premixed combustion. Besides, results for effusion holes in different inclination angle (90° and 30°) are compared. The results indicate that a region with low overall cooling effectiveness on the both liners for normal effusion holes due to the swirling flame impingement effect. Because of double length-to-diameter ratio, inclined holes at 30 degree perform better cooling protection than the normal holes. The variation of equivalence ratio induces the change of the flame pattern, temperature field and flow field, which will have an impact on the liner effusion cooling in consequence.